OPTIMALISASI SISTEM INVENTORY DAN TRACEABILITY PRODUK BERBASIS WEB DENGAN INTEGRASI QR CODE PADA UMKM DAPOER NJOWO - Nurdiana Handayani; Donny Firmansyah; Hengki Rusdianto (Jurnal Teknik, 2026)
The Dapoer Njowo MSME currently manages inventory using a semi-computerized spreadsheet-based system, which supports basic record-keeping but has limitations in efficiency, system integration, and data security. This research aims to design and develop a web-based inventory and product traceability system integrated with QR Codes to improve data management efficiency and enhance product information transparency. The system was developed using the Scrum methodology, with Laravel as the backend framework, Vue.js and TypeScript for the frontend, and Python with FastAPI for QR Code generation. The application is capable of recording raw material flows, production processes, and distribution activities in an integrated manner, and includes a product recall feature. The traceability feature enables consumers to scan QR Codes on product labels to access detailed information, such as product name, batch number, production and expiration dates, certification, manufacturer details, distribution history, and raw material information. The implementation of this system supports more efficient, accountable, and transparent data management for the MSME.